Quality performance of rapid bus operation in Georgetown, Penang / Fazeera Zul’ Azman … [et al.] - Azman, Fazeera Zul’; Nadzri, Nurul Afizah; Ismail, Junaida; Azizan, Intan Syahriza (Universiti Teknologi MARA, 2022)
Service quality is an evaluation of how well a delivered service fulfilled client's expectations. The theory of “service quality” depends on several factors. This study, the researchers have relied on SERVQUAL attributes which comprise reliability, responsiveness, empathy, tangible and assurance. An overview concerning poor service quality provided by Rapid Bus has lessen the confidence of users to use public bus in Georgetown, Penang. In accordance with problems arise mentioned, seven main objectives were determined to analyze level of service quality in this empirical study. Since the sample size is large, this research has been conducted using non-probability sampling technique. Also, cross-sectional survey has been applied to collect data from 417 respondents. The data acquired was evaluated by using correlation and regression technique. This indicator is a proper tool to determine service quality by taking respondents' expectations and perceptions on service quality offer. Additionally, the arrangement of questionnaire consists of Section A (demographic of respondents), Section B (service quality) and Section C until G (SERVQUAL). In this study, the main finding views that responsiveness is the most dominant dimension which affects service quality of Rapid Bus in Georgetown, Penang.